AKTIVITAS MEDIA RELATIONS KEDOKTERAN2019 - Amelia Fernandha; Renata Anisa; Suharjo Nugroho (Jurnal Ranah Komunikasi, 2020)
The growth of the run community triggered the rise of running events in Indonesia. Ironically in the last year, five running events claimed the death fatality in Indonesia has been widely exposed by the national media. In an effort to reduce the fatality rate in the run, KedokteRAN2019 is aware of the importance of media roles to provide the right health information to the public. Based on this, KedokteRAN2019 selected media relations activities as one of the ideal communication strategy. In the implementation of media relations activities, KedokteRAN2019 chose Imogen PR & Digital as a public relations consulting firm. This research aims to describe the process of media relations activities KedokteRAN2019 based on the stage of public relations activities according to Cutlip, through research, planning, implementation, and evaluation. The study uses a qualitatively descriptive method, where researchers describe the reality that goes into research. This research technique uses interview techniques, documentation, and observation. The results showed that at the research, planning, implementation until the evaluation of KedokteRAN2019 has successfully implemented media relations activities. The results were obtained from several instruments of success (key performance indicator) based on the number of media attendance, media coverage of exposure, and the amount of PR value of the activity KedokteRAN2019.